Coconut pulp waste extract (cocos nucifera l.) as corrosion inhibitor for mild steel in 1.0 M acid corrosion - Rahim, Norin Hafizah (2017)
Corrosion control method, especially the use of inhibitors has gained monumental importance nowadays. The demand for green inhibitor to replace toxic one has increased tremendously. The use of local wastes which are organic in nature for the production of green corrosion inhibitor is no doubt the trend of the day. To arrive at an inexpensive, non-toxic and eco-friendly inhibitor formulation, the present study on the use of coconut pulp waste extract of Cocos nucifera L. has been carried out. Coconut pulp waste were chosen to be extracted and investigated in terms of their corrosion inhibition efficiencies for mild steel in 1.0 M HCl using weight loss analysis at different inhibitor concentrations and immersion time, tafel polarization curve and impedance curve at different inhibitor concentrations. The interaction between inhibitor and specimen surface was study using Langmuir, Freundlich and Temkin adsorption isotherms. Weight loss measurement were conducted at different of immersion time which is at 6, 12, 18, 24 and 48 hours. Result from weight loss study showed that as the concentration of the inhibitor increases, the rate of corrosion decreases. It also showed that as the concentration of the inhibitor increases, the inhibition efficiency also increases up to 94.52 %. Further examination study using scanning electron microscopy (SEM) showed the deposition of coconut pulp extract on the metal surface. In potentiodynamic polarization method and electrochemical impedance spectroscopy the electrochemical measurement were carried out using Autolab Potentiostat/Galvonastat. The experiments were conducted using 250 ml of electrolyte (1 M HCl) without and with different concentrations of the extracts of 2, 4, 6, 8, and 10 % v/v. The obtained inhibition efficiencies of extracts from polarization measurements was 89.38 % and 83.47 % from the impedance measurement. The impedance measurement revealed that when the concentration of the coconut pulp increased the charge transfer resistance increased and the double layer capacitance decreased. In polarization measurement the value from corrosion current Ecorr suggested that coconut pulp extract is a mixed type nature of the inhibitor molecules. The adsorption interaction between the corrosion inhibitor with mild steel surface obey the Langmuir adsorption isotherm as the value of the correlation coefficient (R2) is very near to unity. From the value of free energy of adsorption (ΔG°ads) showed a spontaneous adsorption and physisorption process is occurred.